2006
DOI: 10.1242/jeb.02524
|View full text |Cite
|
Sign up to set email alerts
|

PKCγ knockout mouse lenses are more susceptible to oxidative stress damage

Abstract: SUMMARY Cataracts, or lens opacities, are the leading cause of blindness worldwide. Cataracts increase with age and environmental insults, e.g. oxidative stress. Lens homeostasis depends on functional gap junctions. Knockout or missense mutations of lens gap junction proteins, Cx46 or Cx50, result in cataractogenesis in mice. We have previously demonstrated that protein kinase Cγ (PKCγ) regulates gap junctions in the lens epithelium and cortex. In the current study, we further determined whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…Because gap junctions are used in cell-tocell communication pathways, PKCγout mice display learning deficits, insensitivity to pain, do not develop tolerance to alcohol like normal mice ( Abeliovich, et al, 1993), and are more sensitive to hydrogen peroxide induced cataract formation (Lin, 2006). It is thought that these deficits are partially a result of the improper control of gap junctions due to loss of PKCγ (Lin, et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Because gap junctions are used in cell-tocell communication pathways, PKCγout mice display learning deficits, insensitivity to pain, do not develop tolerance to alcohol like normal mice ( Abeliovich, et al, 1993), and are more sensitive to hydrogen peroxide induced cataract formation (Lin, 2006). It is thought that these deficits are partially a result of the improper control of gap junctions due to loss of PKCγ (Lin, et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Lens gap junction coupling is implicated to be responsive to oxidative stress. Activation of PKC␥ by oxidative stress results in phosphorylation of Cx50 and inhibition of gap junctions, whereas uncontrolled opening of gap junctions resulting from PKC␥ deficiency leads to fiber cell damage (34). Our study, for the first time, showed that truncation of Cx50 by caspase-1 or -3 can protect lens cells against UV radiation.…”
Section: Discussionmentioning
confidence: 63%
“…We have previously demonstrated that PKCγ serves as an oxidative stress sensor through proper control of gap junctions in the lens (Lin et al, 2003a(Lin et al, & b, 2004Lin and Takemoto, 2005;Zampighi et al, 2005;Lin et al, 2006). We have also observed that the PKCγ H101Y C1B mutant is not activated by oxidative stress, e.g.…”
Section: Discussionmentioning
confidence: 72%
“…We have previously determined that gap junctions, Cx43 and Cx50, are the major targets of activated PKCγ in the lens epithelial cells in culture and in the whole lens Lin et al, 2003aLin et al, & b, 2004Zampighi et al, 2005). Loss of control of gap junctions by PKCγ, ie., no PKCγ phosphorylation of Cx50 in PKCγ knockout lenses, causes PKCγ knockout lenses to be more susceptible to oxidative stress-induced cataracts in the mouse (Lin et al, 2006). Inhibition of gap junctions prevents cell death (Farahani et al, 2005;de Pina-Benabou et al, 2005;Krysko et al, 2005).…”
Section: Introductionmentioning
confidence: 99%